Surgical Management of Cholecystoenteric Fistula in Patients With and Without Gallstone Ileus: An Experience of 29 Cases - Shi-fei Huang; Ye-hong Han; Jie Chen; Jun Zhang; Hai Huang (Frontiers in Surgery, 2022)
BackgroundCholecystoenteric fistula (CEF) is an uncommon complication of cholelithiasis. Here, we report our experience on diagnostic methods and surgical management of CEF patients with and without gallstone ileus (GI).MethodsThis is a retrospective cases series over an 11-year period (2011–2022). Data analyzed included preoperative characteristics, ultrasound, imaging features, operation findings and postoperative course.ResultsA total of 29 patients diagnosed with CEF were enrolled, 51.7% (15/29) of whom were female, with a median age of 66 years (range: 35–96 years). With regards to subtype distribution, seventeen patients had cholecystoduodenal fistula (CDF), six had cholecystoconlonic fistula (CCF), three exhibited cholecystogastric fistula (CGF), one CDF combination with CCF and two CDF combination with type I Mirizzi syndrome. Twelve patients presented with gallstone ileus, and received one stage procedure or simple Enterolithotomy. The median operation time and blood loss of 157 min (range: 65–360 min) and 40 ml (range: 10–450 ml), respectively. Surgical complications, evidenced by fistula recurrence, were recorded in three patients (3/22; 13.6%), while four (4/29; 13.8%) and one patient (1/29; 3.4%) presented with wound infection and residual stone in common bile duct, respectively. No deaths were reported in our study.ConclusionCEF is a rare complication of gallstone disease that is occasionally found during operation. To date, no consensus has been reached regarding efficacious treatment therapies for CEF patients. For a CEF patient with GI, one stage procedure should be selected prudently, while simple Enterolithotomy would be a mainstream choice for relieving bowel obstruction.